2017
DOI: 10.1016/j.ijmedinf.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Delivering healthcare at a distance: Exploring the organisation of calls to a health helpline

Abstract: Findings from this study suggest that there are systematic differences between the overall structure of health helplines and physically co-present primary care consultations. We demonstrate that the delivery of health information and advice via helplines can be challenging, but that service can be enhanced through continued efforts to inform understanding about how medical encounters routinely unfold in over-the-phone environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
1
26
0
2
Order By: Relevance
“…Our findings support those of previous quantitative and qualitative studies. In line with the work of qualitative researchers (see Lopriore et al, 2017;Murdoch et al, 2015;Turnbull et al, 2012; in similar telephone service settings, our conversation analysis revealed interactional workability issues. Our results suggest that communication misalignment instances have the capacity to increase the risk of system failure and in certain circumstances lead to negative outcomes such as those identified by Rees et al, (2017) in their review of serious incidents involving sick children.…”
Section: Conclusion Implications and Future Researchsupporting
confidence: 76%
See 2 more Smart Citations
“…Our findings support those of previous quantitative and qualitative studies. In line with the work of qualitative researchers (see Lopriore et al, 2017;Murdoch et al, 2015;Turnbull et al, 2012; in similar telephone service settings, our conversation analysis revealed interactional workability issues. Our results suggest that communication misalignment instances have the capacity to increase the risk of system failure and in certain circumstances lead to negative outcomes such as those identified by Rees et al, (2017) in their review of serious incidents involving sick children.…”
Section: Conclusion Implications and Future Researchsupporting
confidence: 76%
“…Telehealth services are an increasingly common facet of contemporary healthcare, with use rising steadily in recent years (Lopriore et al, 2017). Services available over the telephone include those typically offered in the more familiar context of primary care consultations, for example, triage, physical assessment, and treatment recommendations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para minimizar as desigualdades de acesso aos serviços de saúde e aumentar a resolutividade da atenção primária, o Brasil segue a tendência global de desenvolvimento e disseminação da telessaúde, também denominada de telemedicina ou e-saúde, sendo líder na implementação de projetos de grande escala 5,6 . A telessaúde tem sido cada vez mais incorporada como prática rotineira nos serviços de saúde em todo o mundo [7][8][9] . Todavia, ainda existe grande variabilidade na prestação dos serviços e na concepção que profissionais de saúde e usuários declaram sobre o tema 9 .…”
Section: Introductionunclassified
“…Todavia, ainda existe grande variabilidade na prestação dos serviços e na concepção que profissionais de saúde e usuários declaram sobre o tema 9 . Mesmo na Inglaterra, onde o Serviço Nacional de Saúde definiu uma política própria sobre o tema, existem barreiras ao funcionameno pleno das atividades e receio dos médicos diante das novas relações estabelecidas 7 . Outros autores registram também que evidências favoráveis à telessaúde naquele país são variáveis e/ou limitadas, principalmente porque inclui uma ampla gama de tecnologias 10 .…”
Section: Introductionunclassified